MAKNA PENDIDIKAN AGAMA KRISTEN DALAM ALKITAB - Steven Tubagus (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2021)
This paper aims to describe the meaning of Christian Religious Education in the Bible. The method used is text analysis following the principles of exegesis. The results are: First, the knowledge gained is that believers always rely on God in their lives and are blameless so that they receive God's Revelation. God's revelation affects everyone, both believers and non-believers. The words of Revelation have so much weight and power. Second, those who know Jesus have life in God because Jesus said this is eternal life. Christian religious education seeks to unite humans with God. All education is religious; there is nothing from everything that exists in the field of human life that is not controlled and controlled by religion. That education begins in each household and is explained in public services and the teaching of Jesus Christ. Third, because God so loved the world, that He gave His only begotten Son so that everyone who believes in Him should not perish but have eternal life. Receiving the promise is receiving eternal life.